"One-to-three" droplet generation in digital microfluidics for parallel chemiluminescence immunoassays. Issue 15 (1st July 2021) - Jin, Kai; Hu, Chenxuan; Hu, Siyi; Hu, Chengyou; Li, Jinhua; Ma, Hanbin
Abstract : A "one-to-three" splitting method is able to generate sub-microlitre droplets beyond the "well-known" geometry limit in EWOD digital microfluidics. It helps to realise parallel on-chip CLIA with enhanced magnetic beads washing efficiency. Abstract : In digital microfluidics, droplet generation is a fundamental operation for quantitative liquid manipulation. The generation of well-defined micro-droplets on a chip with restricted device geometries has become a real obstacle for digital microfluidics platforms to be used in parallel for in vitro diagnostic applications. Here, we propose a "one-to-three" droplet splitting technique that is able to generate sub-microlitre droplets beyond the "well-known" geometry limit in electrowetting-on-dielectric digital microfluidics. Accordingly, we realized an on-chip magnetic bead chemiluminescence immunoassay for parallel detection with the "one-to-three" technique. With the help of the generated micro droplets, we were able to retain the magnetic beads by a significantly reduced magnetic force. We have shown the detection of five B-type natriuretic peptide analyte samples on a single chip for around 10 minutes. The correlation coefficient of the calibration curve was 0.9942, and the detection limit was lower than 5 pg mL −1 .